Effects of a Low‐Salt and High‐Potassium Diet on Arterial Stiffness and Left Ventricular Function in Indigenous Papuans - Akio Ishida (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background A sodium‐restricted diet represents a potential non‐pharmacological strategy for improving blood pressure, arterial stiffness, and left ventricular (LV) diastolic function. We investigated age‐related differences in LV structure and function and the relationship between LV function and central hemodynamics in an indigenous Papuan population, who maintain a traditional lifestyle, including a low‐salt and high‐potassium diet. Methods and Results We measured LV dimensions, transmitral blood flow, and mitral annular tissue velocities through echocardiography and Doppler imaging. Blood pressure and brachial‐ankle pulse wave velocity were measured using an automatic device (Omron). Central blood pressure and wave reflection parameters were estimated via oscillometry (Mobil‐O‐Graph, using European calibrations). A total of 82 native Papuans (median age, 42 years; 38 women; no blood pressure treatment) were enrolled. Age‐related difference in brachial systolic pressure was modest but significant, and brachial‐ankle pulse wave velocity significantly increased with age; however, LV mass index remained unchanged. LV ejection fraction and global longitudinal strain were preserved; mitral A‐wave velocity and average E/e´ increased; and e´ and E/A decreased with age. Brachial‐ankle pulse wave velocity and spot urine Na/K were positively and independently correlated with E/e´. Age and heart rate were inversely associated with E/A. In conclusion, LV systolic function was preserved; however, LV diastolic function decreased with age in Papuans. Moreover, age‐related arterial stiffening, but not wave reflections, was inversely related to LV diastolic function. Conclusions Our results suggest that arterial and LV stiffness may not be altered by sodium restriction. Longitudinal studies are warranted to elucidate the effects of diet on arterial and LV function.